Developing a simple distributed sensor system for automated online monitoring and alerting:Case study of TVOC sensor network system prototype development for real-time monitoring and alerting of air quality in operations - Thuamjorn, Chanok (Bulletin of Applied Sciences, 2022)
This work demonstrates the development of a smart TVOC sensor network. A smart TVOC sensor system is designed using MOS type TVOC sensors, a logic level converter circuit, VPS and IoT-related open-source software including IoT broker, IoT gateway and MQTT API. The system is used as a prototype for smart sensors which plays a crucial role in the development of the cyber-physical system. The final spin-off of the development is capable to create near real-time TVOC concentration data records, online TVOC concentration reports on IoT dashboard, and online TVOC concentration reports on mobile messenger applications, making it more advantageous than traditional standalone TVOC detectors. By taking advantage of the development, a TVOC smart sensor could help control air pollution in the workspace becomes more efficient. Data from the system composed of 3 TVOC sensors, in this work, are collected and analyzed to replicate the measurement uncertainty model and covariance analysis within groups.The result shows that the system exhibits a weak correlation (R2< 0.9) which is commonly due to a tradeoff between the standalone sensor and distributed sensor. Consequently, data pre-processing and normalization are necessarily required for the further development of a smart TVOC sensor network.